2023
DOI: 10.1007/s40120-023-00475-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dimethyl Fumarate in Young Adults with Relapsing-Remitting Multiple Sclerosis: Analysis of the DEFINE, CONFIRM, and ENDORSE Studies

Abstract: Introduction: Dimethyl fumarate (DMF) showed favorable benefit-risk in patients with relapsing-remitting multiple sclerosis (MS) in phase 3 DEFINE and CONFIRM trials and in the ENDORSE extension study. Disease activity can differ in younger patients with MS compared with the overall population. Methods: Randomized patients received DMF 240 mg twice daily or placebo (PBO; years 0-2 DEFINE/CONFIRM), then DMF (years 3-10; continuous DMF/DMF or PBO/DMF; ENDORSE); maximum follow-up (combined studies) was 13 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Additional information regarding the safety and efficacy of DMF for MS patients comes from several postmarketing real-world studies and retrospective analyses [37][38][39][46][47][48][49][50][51]. One of these studies, PROTEC, investigated the effectiveness of DMF on disease activity and patient-reported outcomes (PROs) in patients with RRMS [46].…”
Section: Mmf Efficacy and Tolerabilitymentioning
confidence: 99%
“…Additional information regarding the safety and efficacy of DMF for MS patients comes from several postmarketing real-world studies and retrospective analyses [37][38][39][46][47][48][49][50][51]. One of these studies, PROTEC, investigated the effectiveness of DMF on disease activity and patient-reported outcomes (PROs) in patients with RRMS [46].…”
Section: Mmf Efficacy and Tolerabilitymentioning
confidence: 99%